Reduction in Hindquarter Vascular Resistance Supports 5-HT7 Receptor Mediated Hypotension - Seitz, Bridget M.; Watts, Stephanie W.; Fink, Gregory D. (Frontiers in Physiology, 2021)
The 5-HT7 receptor is the primary mediator of both the acute (<hours) and chronic (day-week) decreases in mean arterial pressure (MAP) during low dose 5-HT infusion in rats. Previous data show the hypotensive response during chronic 5-HT infusion is due to a decrease total peripheral resistance (TPR) and specifically splanchnic vascular resistance. We hypothesized that changes in vascular resistance in both the splanchnic and skeletal muscle vascular beds are critical to the cardiovascular effects mediated by the 5-HT7 receptor. Systemic and regional hemodynamic data were collected in conscious and anesthetized male rats using radiotelemetry, vascular catheters and transit-time flowmetry. Reversible antagonism of the 5-HT7 receptor was achieved with the selective antagonist SB269970 (33 μg/kg, iv). From the very beginning and throughout the duration (up to 5 days) of a low dose (25 μg/kg) infusion of 5-HT, TPR, and MAP were decreased while cardiac output (CO) was increased. In a separate group of rats, the contribution of the 5-HT7 receptor to the regional hemodynamic response was tested during 5-HT-induced hypertension. The decrease in MAP after 24 h of 5-HT (saline 83 ± 3 vs. 5-HT 72 ± 3 mmHg) was associated with a significant decrease in skeletal muscle vascular resistance (saline 6 ± 0.2 vs. 5-HT 4 ± 0.4 mmHg/min/mL) while splanchnic vascular resistance was similar in 5-HT and saline-treated rats. When SB269970 was administered acutely, MAP and skeletal muscle vascular resistance rapidly increased, whereas splanchnic resistance was unaffected. Our work suggests the most prominent regional hemodynamic response to 5-HT7 receptor activation paralleling the fall in MAP is a decrease in skeletal muscle vascular resistance.